Structural characterization and Curie temperature determination of a sodium strontium niobate ferroelectric nanostructured powder - Lanfredi, Silvania [UNESP]; Genova, Diego H. M. [UNESP]; Brito, Iara A. O. [UNESP]; Lima, Alan R. F.; Nobre, Marcos Augusto Lima [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
The Curie temperature and its correlation with the magnitude of the displacement of the niobium atom from the center of [NbO6] octahedra in NaSr2Nb5O15 nanostructured powder were investigated. A single powder was prepared by high-energy ball milling. A powder with an average crystallite size of 37 nm was prepared by calcining the precursor at 1423 K. The refinement of the structural parameters was carried out by the Rietveld method. NaSr2Nb5O15 exhibits tetragonal symmetry with the tungsten bronze structure (a=b=12.3495 (6)angstrom, c=3.8911 (2)angstrom, V-593.432 (5) angstrom(3), and Z=2). The site occupancy of the Na and Sr2+ cations and the interatomic distances between the niobium and oxygen atoms were derived. The [NbO6] octahedron undergoes both rotation and tilting depending on the crystallographic site. The Curie temperature of the powder was derived using both the impedance and infrared spectroscopy methods. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Nanostructured powder; Rietveld method; Infrared spectroscopy; Impedance spectroscopy; Ferroelectric; Curie temperature